Supplier concentration and corporate innovation input - Zou, Meifeng; Zhang, Xindong (Frontiers in Psychology, 2022)
We study the relationship between supplier concentration and corporate innovation: a firm with higher supplier concentration tends to lower R&D expenditure and invention patents. Considering endogenous problems, this negative relationship is still robust by using the instrumental variable regression and propensity score matching method. Mechanism analysis shows that supplier concentration affects corporate innovation through risk-taking channel, occupied resource channel, and bargaining power channel. Our evidence shows that a deeper exposure to a small set of large supplier bears negative consequences for the firm. This paper sheds new light on the dark side of high level of supplier concentration on corporate innovation.